Relações de cuidado entre avós, em paliação, e netos cuidadores. - Medeiros, Waleska de Carvalho Marroquim (2019)
Advances in the field of health over the last decades have caused profound changes in the world’s population, which gets older year by year. This demands integrated actions aimed at assisting the elderly who, as they age, become more vulnerable to incapacitating chronic degenerative illnesses. As they become more incapacitated, they need more assistance, making them more dependent on technical and human resources that intend to offer quality of life, given that the aging process cannot be reversed. Thus, geriatric palliative care looks forward to observing illnesses developed in this stage of life as a whole, with comfort and wellbeing as the main focus of its intervention, including family members from the diagnosis until after the death of the elderly patient. With ever smaller families and ever older elderlies, some other actors have been invited to greater involvement, among them the grandchildren. Objective: The objective of this thesis is to comprehend the relationship established between grandparents in palliative care and their caretaker grandchildren. Method: This research is exploratory in nature, using a qualitative approach. It was carried out with seven pairs of grandparents in palliative care and their caretaker grandchildren. The instruments used were a semi-structured interview, sociodemographic survey data, and a field diary. The data were analysed using Bematic Content Analysis with systemic perspective. Results: The research indicated that 1) the relationships among the pairs were already satisfactory since the grandchildren’s childhood, but grew even closer after the grandchildren became caretakers; 2) the tensions due to the hierarchical inversion were smaller than the satisfaction shown in the exchange and intergenerational care; 3) spirituality and social support networks (friends, romantic partners, relatives, professionals) were sought by grandparents and grandchildren to deal with the stressful situation provoked by the processes of aging, illness, and palliative care; 4) the parents’ generation offered support and stimulated these relationships, except in families with triangulation and coalitions; 5) there was reciprocity in care between the two generations in analysis, such that caring for their grandparents was an important factor for the grandchildren. Final Considerations: Whether due to affinity, proximity, gratitude, solidarity, reciprocity, or convenience, the grandchildren show satisfaction in the task of taking care of their grandparents, and also felt taken care of by them. The intermediate generation appeared to favour the grandchildren becoming closer to their grandparents due to the special condition of caregivers. Even though loss of autonomy appears to be the main stress factor experienced by the grandparents, the opportunity of being beside their grandchildren was shown to be more important than the hierarchical inversion provoked by the change in caretaking roles. Therefore, both for the grandparents and for the grandchildren, the positive aspects were more prominent, reinforcing that it is, in fact, affection that sustains these intergenerational relations.